An old friend with a new face: YB-1 and its role in healthy pregnancy and pregnancy-associated complications - Fischer, Florence; Schumacher, Anne; Meyer, Nicole; Fink, Beate; Bauer, Mario; Stojanovska, Violeta; Zenclussen, Ana Claudia (Frontiers in Cell and Developmental Biology, 2022)
By promoting tissue invasion, cell growth and angiogenesis, the Y-box binding protein (YB-1) became famous as multifunctional oncoprotein. However, this designation is telling only part of the story. There is one particular time in life when actual tumorigenic-like processes become undoubtedly welcome, namely pregnancy. It seems therefore reasonable that YB-1 plays also a crucial role in reproduction, and yet this biological aspect of the cold-shock protein has been overlooked for many years. To overcome this limitation, we would like to propose a new perspective on YB-1 and emphasize its pivotal functions in healthy pregnancy and pregnancy-related complications. Moreover, we will discuss findings obtained from cancer research in the light of reproductive events to elucidate the importance of YB-1 at the feto-maternal interface.